Moderately and Late Preterm Infants: Short- and Long-Term Outcomes From a Registry-Based Cohort - Smyrni, Nikoletta; Koutsaki, Maria; Petra, Marianna; Nikaina, Eirini; Gontika, Maria; Strataki, Helen; Davora, Fotini; Bouza, Helen; Damianos, George; Skouteli, Helen; Mastroyianni, Sotiria; Dalivigka, Zoi; et al. (Frontiers in Neurology, 2021)
While most studies on the association of preterm birth and cerebral palsy (CP) have focused on very preterm infants, lately, attention has been paid to moderately preterm [(32 to <34 weeks gestational age (GA)] and late preterm infants (34 to <37 weeks GA). In order to report on the outcomes of a cohort of moderately and late preterm infants, derived from a population-based CP Registry, a comparative analysis of data on 95 moderately preterm infants and 96 late preterm infants out of 1016 with CP, was performed. Moderately preterm neonates with CP were more likely to have a history of N-ICU admission (p=0.001) and require respiratory support (p<0.001) than late preterm neonates. Birth weight was significantly related to early neonatal outcome with children with lower birth weight being more likely to have a history of N-ICU admission [moderately preterm infants (p=0.006) / late preterm infants (p<0.001)], to require ventilator support [moderately preterm infants (p=0.025) / late preterm infants (p=0.014)] and not to have neonatal seizures [moderately preterm infants (p=0.044) / late preterm infants (p=0.263)]. In both subgroups, the majority of children had bilateral spastic CP with moderately preterm infants being more likely to have bilateral spastic CP and less likely to have ataxic CP as compared to late preterm infants (p=0.006). The prevailing imaging findings were white matter lesions in both subgroups, with statistically significant difference between moderately preterm infants who required ventilator support and mainly presented with this type of lesion versus those who did not and presented with grey matter lesions, maldevelopments or miscellaneous findings. Gross motor function was also assessed in both subgroups without significant difference. Among late preterm infants, those who needed N-ICU admission and ventilator support as neonates achieved worse fine motor outcomes than those who did not. Low birth weight is associated with early neonatal problems in both moderately and late preterm infants with CP. The majority of children had bilateral spastic CP and white matter lesions in neuroimaging. GMFCS levels were comparable in both subgroups while BFMF was worse in late preterm infants with a history of N-ICU admission and ventilator support.